Phase response curve to 1 h light pulses for the European rabbit (Oryctolagus cuniculus). (13th September 2016) - Kennedy, Gerard A.; Hudson, Robyn
ABSTRACT: While much is known about the circadian systems of rodents, chronobiological studies of other mammalian groups have been limited. One of the most extensively studied nonrodent species, both in the laboratory and in the wild, is the European rabbit. The aim of this study was to extend knowledge of the rabbit circadian system by examining its phasic response to light. Twelve Dutch-Himalayan cross rabbits of both sexes were allowed to free-run in constant darkness and then administered 1 h light pulses (1000 lux) at multiple predetermined circadian times. Changes in the phase of the rabbits' circadian wheel-running rhythms were measured after each light pulse and used to construct a phase–response curve (PRC). The rabbits' PRC and free-running period ( τ ) conformed to the empirical regularities reported for other predominantly nocturnal animals, including rodents and predatory marsupials. The results of the study are thus consistent with reports that the rabbit is essentially a nocturnal animal and show that it can entrain to light/dark (LD) cycles via discrete phase shifts. Knowledge about the rabbit's circadian range of entrainment to LD cycles gained in this study will be useful for examining the putative circadian processes believed to underlie the unusual rhythm of very brief, once-daily nest visits by nursing rabbit mothers and other nursing lagomorphs.